A local O(n2) gathering algorithm - Degener, Bastian; Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Proceedings of the 22nd ACM symposium on Parallelism in algorithms and architectures - SPAA '10)

Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part II.

Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part I.

Network coding in passive optical networks - Miller, Konstantin; Biermann, Thorsten; Woesner, Hagen; Karl, Holger (Network Coding (NetCod), 2010 IEEE International Symposium on)

RiaS: overlay topology creation on a PlanetLab infrastructure - Lischka, Jens; Karl, Holger (Proceedings of the second ACM SIGCOMM workshop on Virtualized infrastructure systems and architectures)

Energy efficiency model of network-coded cooperation in wireless sensor networks - Woldegebreal, Dereje H; Karl, Holger (Sensor Technologies and Applications (SENSORCOMM), 2010 Fourth International Conference on)

Cooperative communication to improve reliability and efficient neighborhood wakeup in wireless sensor networks - Khan, Rana Azeem M; Karl, Holger (Proceedings of the Fourth International Conference on Mobile Ubiquitous Computing (UBICOMM 2010))

Bayes optimal multilabel classification via probalistic classifier chains - Dembczynski, K.; Cheng, W.; Hüllermeier, Eyke (in Proceedings ICML-2010, 27th International Conference on Machine Learning, Haifa, Israel)

Label ranking based on the Plackett-Luce model - Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (in Proceedings ICML-2010, 27th International Conference on Machine Learning, Haifa, Israel)

Graded multi-label classification: The ordinal case - Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (in Proceedings ICML-2010, 27th International Conference on Machine Learning, Haifa, Israel)

Regret analysis for performance metrics in multi-label classification: The case of Hamming and subset zero-one loss - Dembczynski, K.; Waegeman, W.; Cheng, W.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-2010, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, ,Bareclona, Spain)

Predicting partial orders: Ranking with abstention - Cheng, W.; Rademaker, M.; De Beats, B.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-2010, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, ,Bareclona, Spain)

Uncertainty in clustering and classification - Hüllermeier, Eyke (in Proceedings SUM 2010, International Conference on Scalable Uncertainty Management)

A Triple Hybrid Interconnect for Many-Cores: Reconfigurable Mesh, NoC and Barrier - Giefers, Heiner; Platzner, Marco (Proceedings of the 20th International Conference on Field Programmable Logic and Applications (FPL))

Engineering Self-Coordinating Software Intensive Systems - Schäfer, Wilhelm; Birattari, Mauro; Blömer, Johannes; Dorigo, Marco; Engels, Gregor; O'Grady, Rehan; Platzner, Marco; Rammig, Franz-Josef; Reif, Wolfgang; Trächtler, Ansgar (Proceedings of the Foundations of Software Engineering (FSE) and NITR & D/SPD Working Conference on the Future of Software Engineering Research (FoSER))

A Self-Reconfigurable Lightweight Interconnect for Scalable Processor Fabrics - Giefers, Heiner; Platzner, Marco (Proceedings of the 10th International Conference on Engineering of Reconfigurable Systems and Algorithms (ERSA))

Closing the Gap between UML-based Modeling and Simulation of Combined HW/SW Systems - Mischkalla, Fabian; He, Da; Müller, Wolfgang (Proceedings of DATE’10)
UML is widely applied for the specification and modeling of software and some studies have demonstrated that it is applicable for HW/SW codesign. However, in this area there is still a big gap from UML modeling to SystemC-based verification and synthesis environments. This paper presents an efficient approach to bridge this gap in the context of Systems-on-a-Chip (SoC) design. We propose a framework for the seamless integration of a customized SysML entry with code generation for HW/SW cosimulation and high-level FPGA synthesis. For this, we extended the SysML UML profile by SystemC and synthesis capabilities. Two case studies demonstrate the applicability of our approach.
Keywords: Unified modeling language; Field programmable gate arrays; Bridges; Helium; Real time systems; Operating systems; Documentation; Application software; XML; Space exploration

Assertion-Based Verification of RTOS Properties - Oliveira, Marcio F. S.; Zabel, Henning; Müller, Wolfgang (Proceedings of DATE’10)
Today, mobile and embedded real time systems have to cope with the migration and allocation of multiple software tasks running on top of a real time operating system (RTOS) residing on one or several processors. For scaling of each task set and processor configuration, instruction set simulation and worst case timing analysis are typically applied. This paper presents a complementary approach for the verification of RTOS properties based on an abstract RTOS-Model in SystemC. We apply IEEE P1850 PSL for which we present an approach and first experiences for the assertion-based verification of RTOS properties.
Keywords: Operating systems; Real time systems; Timing; Hardware; Analytical models; Embedded software; Software systems; Processor scheduling; Software performance; Performance analysis

Timing Modeling and Analysis for AUTOSAR-Based Software Development - A Case Study - Klobedanz, Kay; Kuznik, Christoph; Thuy, Andre; Müller, Wolfgang (Proceedings of DATE’10, Dresden)
Safety-critical automotive systems must fulfill hard real-time constraints for reliability and safety. This paper presents a case study for the application of an AUTOSAR-based language for timing modeling and analysis. We present and apply the Timing Augmented Description Language (TADL) and demonstrate a methodology for the development of a speed-adaptive steer-by-wire system. We examine the impact of TADL and the methodology on the development process and the suitability and interoperability of the applied tools with respect to the AUTOSAR-based tool chain in the context of our case study.
Keywords: Timing; Programming; Automotive engineering; Application software; Hardware; Computer architecture; Communication system software; Software architecture; Delay; Software standards

A Systematic Approach to Combined HW/SW System Test - Krupp, Alexander; Müller, Wolfgang (Proceedings of DATE’10)
Today we can identify a big gap between requirement specification and the generation of test environments. This article extends the Classification Tree Method for Embedded Systems (CTM/ES) to fill this gap by new concepts for the precise specification of stimuli for operational ranges of continuous control systems. It introduces novel means for continuous acceptance criteria definition and for functional coverage definition.
Keywords: System testing; Automatic testing; Object oriented modeling; Classification tree analysis; Automotive engineering; Mathematical model; Embedded system; Control systems; Electronic equipment testing; Software testing